2009
DOI: 10.1063/1.3205006
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Nd substitution on the electrical properties of Bi3NbTiO9 Aurivillius phase ceramics

Abstract: Effect of lattice occupation behavior of Li+ cations on microstructure and electrical properties of (Bi1/2Na1/2)TiO3-based lead-free piezoceramics J. Appl. Phys. 109, 054102 (2011) The effect of Nd substitution on the microstructures and electrical properties of Aurivillius phase ferroelectric Bi 3 NbTiO 9 -based ceramics has been studied. All of the Bi 3−x Nd x NbTiO 9 ͑0 Յ x Յ 1͒ ceramics are ferroelectrics. The Curie point T C decreased with increasing Nd doping content x. The Bi 3−x Nd x NbTiO 9 ceramics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 32 publications
1
17
1
Order By: Relevance
“…28 It is of extremely significance to find that the T C of iBNTN-x ceramics is above 750 • C, much higher than that of La-doped iBTN, 11 and even higher than that of Nd-doped BTN. 14 The retarded decrease in anti-symmetry of the structure caused by the substitution of 6S 2 lone pairs of Bi 3+ should be responsible for the better T C retention of Nd 3+ than that of La 3+ , due to their different ionic radii (r Nd 3+ = 1.17 Å , r La 3+ = 1.35 Å , for a coordination number of 12) and electronic states (Nd 3+ : 4f 3 , La 3+ : 4f 0 ). 29 The higher T C of Nd-doped iBTN than that of Nd-doped BTN is attributed to the decreased incorporation of Nd 3+ into the "BTN part" of iBTN, and correspondingly more Nd 3+ incorporated into the "BiT part".…”
Section: Electrical Propertiesmentioning
confidence: 97%
“…28 It is of extremely significance to find that the T C of iBNTN-x ceramics is above 750 • C, much higher than that of La-doped iBTN, 11 and even higher than that of Nd-doped BTN. 14 The retarded decrease in anti-symmetry of the structure caused by the substitution of 6S 2 lone pairs of Bi 3+ should be responsible for the better T C retention of Nd 3+ than that of La 3+ , due to their different ionic radii (r Nd 3+ = 1.17 Å , r La 3+ = 1.35 Å , for a coordination number of 12) and electronic states (Nd 3+ : 4f 3 , La 3+ : 4f 0 ). 29 The higher T C of Nd-doped iBTN than that of Nd-doped BTN is attributed to the decreased incorporation of Nd 3+ into the "BTN part" of iBTN, and correspondingly more Nd 3+ incorporated into the "BiT part".…”
Section: Electrical Propertiesmentioning
confidence: 97%
“…[7][8][9][10][11][12][13][14][15] Chemical doping of perovskite type materials, without producing a large decrease in their Curie temperature ͑T c ͒, has been useful in enhancing their electrical and magnetic properties. 9,[16][17][18][19][20] Mn 3+ doping has been reported to be effective for suppressing leakage current and improving the polarization switching properties of Bi 4 Ti 3 O 12 single crystals. 19 Other workers 9,21 have found that electrical conductivity in Bi 5 Ti 3 Fe 1−x Mn x O 15 ͑x =0-1͒ ceramics increases with x.…”
Section: Introductionmentioning
confidence: 99%
“…With increasing W/Cr doping, the activation energy increased from ~0.9 to ~1.5 eV. This is associated with a change from extrinsic to intrinsic conductivity (Takahashi, 2003;Zhou, 2006;Zhang, 2009). It is well known that the intrinsic electronic conductivity activation energy is equal to half of the energy of the band gap (E g ).…”
Section: W/cr Modified Bi 4 Ti 3 O 12 Ceramicsmentioning
confidence: 98%